IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM UPAYA MENINGKATKAN KREATIVITAS DAN KEMANDIRIAN BELAJAR PESERTA DIDIK KELAS IV PADA MATA PELAJARAN IPAS DI MI DARUL HUDA LEWIHPAPAN - Selpiyana Selpiyana; Siti Munawaroh; Siti Asiah; Kosasih Kosasih; Elan Zaelani Rahman (Staisman Press, 2023)
The importance of active participation from all stakeholders, including parents and the local community in supporting the implementation of MI Darul Huda Lewihpapan Pandeglang Merdeka Curriculum is also an important part of the findings. The close relationship between the school and the community is proven to support the achievement of the Merdeka Curriculum goals, which focus on developing students' holistic skills. The results of this study provide valuable insights for policy makers, educators, related to MI Darul Huda Lewihpapan Pandeglang, Banten, The theoretical approach in this study refers to the concept of learning competence as the main foundation for evaluating the implementation of Merdeka Curriculum at MI Darul Huda Lewihpapan Pandeglang. Learning competencies are understood as a collection of skills, knowledge, and attitudes that create the basis for the achievement of learning objectives. This theory is used to detail how Merdeka Curriculum can shape and improve learners' learning competencies. The research method applied in this study is a qualitative approach. The choice of this method is based on the need to explore participants' understanding and understand the dynamics of interaction between educators and learners. Through in-depth interviews, observations, and content analysis, this study aims to understand more deeply how the implementation of the independent curriculum at MI Darul Huda Lewihpapan is optima and how the independent curriculum affects learners' skills and independence. Qualitative data helps identify changes in learning strategies, learner learning experiences, and classroom dynamics that may arise as a result of implementing the Merdeka Curriculum. By combining learning competency theory and qualitative research methods, this study seeks to provide an in-depth understanding of the implementation of Merdeka Curriculum in Pandeglang, one of which is MI Darul Huda Lewihpapan. The results are expected to contribute to the development of more effective education policies and open the door to further research in curriculum development that is responsive to local needs.